Epidemiology and injectable antiseizure medication treatment patterns of seizure patients treated in United States hospitals - Beaty, Silky; Rosenthal, Ning; Gayle, Julie; Dongre, Prashant; Ricchetti-Masterson, Kristen; Rhoney, Denise H. (Frontiers in Neurology, 2022)
Objective This study aimed to examine the epidemiology of seizures, clinical outcomes, and antiseizure medication treatment patterns among seizure patients treated in United States hospitals. Design A retrospective cross-sectional study was conducted using data from a large geographically diverse hospital discharge database. Setting 860 acute care hospitals in the United States. Participants Patients aged ≥18 years with an outpatient emergency department or inpatient visit between 1 July 2016–31 December 2019 were included. Intervention None. Main outcomes and measures Key outcomes included prevalence of seizure, seizure type, admission point of origin, intensive care unit admission, discharge status, and injectable antiseizure medication utilization. Seizures were identified by the International Classification of Disease, Tenth Revision, Clinical Modification diagnosis codes. Results Among 36,598,627 unique emergency department outpatients (72,372,464 outpatient visits) and 16,543,592 unique inpatients (24,923,489 inpatient admissions) analyzed, seizure was present in 2.1% of outpatients (1.87% of outpatient visits) and 4.9% of inpatients (4.8% of inpatient admissions). In overall seizure patients, 49.1% were unclassified, 4.4% had generalized onset, 2.9% had focal onset, and 42.8% were categorized as other (including 38.5% with convulsion). Among seizure-associated inpatient admissions, <1% were transferred directly from skilled nursing facility or other long-term care facilities but 22.7% were discharged to such facilities. Nearly a third (31%) of all inpatients were admitted to ICU. About 88.3% of patients with injectable ASM use had monotherapy, 4.6% had polytherapy with 1 day or multiple non-consecutive days of overlap, and 7.0% had polytherapy with ≥2 consecutive days of overlap. The percentage of patients with no step down to any oral ASM ranged between 34.0–57.0%. Conclusions Seizures affect a substantial number of hospital-based emergency department outpatient and inpatient encounters and are associated with poor clinical outcomes and significant healthcare burden. Concomitant use of injectable ASMs is uncommon and a high percentage of IV ASM users with a diagnosis of seizure had no step down to oral therapy. Relevance The study findings may inform clinicians and hospital decision makers about current clinical practice and burden of seizures and identify areas to improve overall outcomes for patients with seizures.